Penerapan Metode Kerja Kelompok dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas VIII.F SMP Negeri 12 Mataram - Mukasri, Mukasri (ANWARUL, 2023)
This study aims to find out the results of implementing group study in improving the learning outcomes of Indonesian language students in Class VIII.F at SMP Negeri 12 Mataram in the academic year 2022/2023. This research is a classroom action research. The subjects in this study were 33 students of class VIII.F SMP Negeri 12 Mataram with 19 male students and 14 female students. Data collection techniques used are observation, documentation, and tests. Observations are used to collect data on learning interest. The test is used to measure learning achievement in Indonesian subjects. Data analysis used is descriptive qualitative and descriptive quantitative. The increase in students' cognitive learning outcomes before and after the implementation of group learning at SMP Negeri 12 Mataram can be seen from the percentage gain of each indicator, namely: The average value of the initial data students obtained 73.98% increased to 80.15 in cycle I and obtained 88.06 in cycle II. While students who completed the data of 23 people then obtained 27 in cycle I and experienced an increase to 33 people in cycle II with each classical completeness obtained initial data of 69.64% to 81.82% in cycle I and increased to 100% in cycle II, this shows that all the indicators expected by the researcher on the reading ability of class I students were successfully achieved. Lesson planning carried out by the teacher increased from 75.00% in cycle I and 85.00% in cycle II. So the lesson planning carried out by the teacher is very good. While the implementation of learning carried out by the teacher also experienced an increase from 79.17% in cycle I to 87.50% in cycle II. So the implementation of learning carried out by the teacher has also increased. Student learning activities that the average percentage in the first cycle is 80.00%. But in cycle II, student learning activities increased to 90.00%. So student learning activities in learning Indonesian are good.